Investigating MOOCs Through Blog Mining - Chen, Yong (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
MOOCs (massive open online course) is a disruptive innovation and a current buzzword in higher education. However, the discussion of MOOCs is disparate, fragmented, and distributed among different outlets. Systematic, extensively published research on MOOCs is unavailable. This paper adopts a novel method called blog mining to analyze MOOCs. The findings indicate, while MOOCs have benefitted learners, providers, and faculty who develop and teach MOOCs, challenges still exist, such as questionable course quality, high dropout rate, unavailable course credits, ineffective assessments, complex copyright, and limited hardware. Future research should explore the position of MOOCs and how it can be sustained.